Importance of anaerobic seed germination and seedling development in direct-seeded rice with special reference to Sri Lanka - Illangakoon, T.K.; Marambe, B.; Keerthisena, R. S. K.; Kumar, V. (Sri Lanka Journals Online, 2019)
Direct-seeded rice (DSR) is becoming more popular among paddy farmers but it results in irregular stand establishment and high weed infestation. Early season flooding is another constraint to rice production in tropics as well as some of the major rice-growing areas in global scale and Sri Lanka is not an exception. Ability of some rice (Oryza sativa L.) genotypes to tolerate flooding during germination and seedling growth or anaerobic germination (AG) tolerance could help in overcoming the major obstacles in DSR. The rice cultivars, their mechanisms and the major QTLs governing AG-tolerance have been identified and two genes namely AG1 and AG2 have been incorporated to popular rice varieties for direct use. However, limited attempts have been made to screen Sri Lankan rice entries for AG tolerance. This review emphasizes the progress of AG-tolerance research, current challenges, future prospects as well as the importance of screening and identifying AG-tolerant rice varieties and validating management options to use this technology in DSR system in Sri Lanka.